Milk and milk processing industry in Lithuania: an analysis of horizontal and vertical integration - Angele Kedaitiene; Heinrich Hockmann (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2002)
Despite significant progress in recent years, horizontal and vertical integration of the Lithuanian milk sector is not very much advanced. The primary sector is characterised by small-scale farming, the fragmentation of farmland and a low number of livestock per farms. These features cause severe problems regarding the restructuring and modernisation of agricultural production since only a few farmers possess the capital resources to conduct necessary investments. However, despite the unfavourable conditions Lithuanian milk producers have made significant improvements concerning milk quality. In the last decade, the processing sector was due to drastic concentration processes. These were induced by the strong competition processes on the milk market and fostered by foreign direct investors. Today, the market is dominated by three companies. About ten enterprises supply almost the entire market of dairy products. The main mode of governance in the market for raw milk is contractual arrangements. The spot market of strong vertical control are unimportant. The basic rules of the contracts like duration or payment scheme are set by the Ministry of Agriculture, others, especially prices, are negotiated individually between farmer and processor. Because of advantages in terms of transport and transaction costs processors provide better conditions to large agricultural producers. Often the processors try to strengthen their relationships with large-scale producers by providing credits for farm modernisation and/or foodstuff. Most small producers do not deliver directly to processors but to milk collection centres. In general, these are owned by processors. So far, only a few farmers co-operatives have been established in order to take this function. Contractual arrangements also dominate in the distribution channel. Small processors supply mainly to wholesalers who supply the retail market. Large processors often circumvent the wholesale stage and supply the retail stage directly. The basic means which allow this forward integration are intensive marketing activities which are intended to improve the consumer perception of their products. However, this type of exchange is mainly observed in urban areas where well established large retail chains exist. The Lithuanian milk sector is highly internationally competitive. The expansion to international markets is in the responsibility of the individual firms. However, the Lithuanian government and the food processors have established a joint marketing agency that provides infrastructure and joint marketing for international trade.
urn:nbn:de:gbv:3:2-23196
Keywords: L11; L66; Q13; 330; Horizontal and vertical integration; Lithuanian milk sector; foreign trade; consumption; Milchverarbeitung; Lieferanten-Kunden-Beziehung; Horizontale Konzentration; Vertikale Konzentration; Litauen